Protocol for multiplex immunofluorescence imaging of mouse intestinal tumors - Shuqin Li; Siyuan You; Kairui Mao (STAR Protocols)
Summary: The tumor microenvironment (TME) plays a critical role in both tumor progression and therapeutic efficacy. Here, we present a protocol to perform transcription factor and surface marker staining for a comprehensive analysis of the TME of mouse intestinal tumors by combining multiplex immunofluorescence imaging with the “Swiss roll” technique. We describe steps for sample preparation, sectioning, staining, and mounting. We then detail procedures for imaging and data processing. This protocol supports quantitative assessments such as calculating cell-to-cell distances.For complete details on the use and execution of this protocol, please refer to You et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.